2013
DOI: 10.3109/00207454.2013.796551
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhizin protects spinal cord and reduces inflammation in spinal cord ischemia–reperfusion injury

Abstract: Treatment with glycyrrhizin exerted a neuroprotective effect against spinal cord ischemia-reperfusion injury. The anti-inflammatory effect was believed to be one of the contributing mechanisms. Our findings provided experimental and therapeutic options for the treatment of spinal cord ischemia-reperfusion injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…GA was shown to inhibit HMGB1 production by Kupffer cells and prevented I/R-induced liver injury [40]. GA could also alleviate I/R-induced [41] and spinal cord [42] mechanism. In addition, GA conjugates free radicals, which might explain the protective action of GA [43].…”
Section: Inhibition Of Hepatic Apoptosis and Necrosismentioning
confidence: 96%
“…GA was shown to inhibit HMGB1 production by Kupffer cells and prevented I/R-induced liver injury [40]. GA could also alleviate I/R-induced [41] and spinal cord [42] mechanism. In addition, GA conjugates free radicals, which might explain the protective action of GA [43].…”
Section: Inhibition Of Hepatic Apoptosis and Necrosismentioning
confidence: 96%
“…Furthermore, glycyrrhizin has been reported to attenuate I/R-induced gut, spinal cord, liver and heart damage (914). However, to the best of our knowledge, the effect of glycyrrhizin on I/R-induced renal injury has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the present study indicated that treatment with glycyrrhizin effectively decreased HMGB1 miRNA expression levels in rats with myocardial I/R injury. However, Ni et al (39) reported that the neuroprotective effect of glycyrrhizin prevents spinal cord I/R injury, through inflammatory cytokines and HMGB-1 expression.…”
Section: Discussionmentioning
confidence: 99%